Parental control. La riarticolazione della famiglia attraverso le tecniche di PMA - Piluso, Francesco; Pelusi, Francesco (E|C, 2023)
The aim of the essay is to investigate the Medically Assisted Procreation (MAP), pointing out its role in reassembling the social, through the hybradization of heterogeneous human and non-human actors and the reconfiguration of their relationships. The MAP displays and operates in the articulations of the reproduction process, deconstructing its naturality and immediacy and allowing its knowledge and manipulation. The plurality of temporalities, spaces and actors involved in the MAP opens to new social figures and multiple parental models that often lack social and juridical acknowledgement. In Italy, the Law interprets the role of the MAP according to the heteronormative model of “natural” reproduction, limiting the possibilities offered by this techno-practice. In reference to the work of Latour, the essay highlights the necessity to emancipate the technique and the Law from their engagement to a metaphysical natural or social referent, fostering their capacity to express the multiplicity of reality.